2018
DOI: 10.1080/24701394.2018.1464563
|View full text |Cite
|
Sign up to set email alerts
|

Utility of mitochondrial CO1 sequences for species discrimination of Spirotrichea ciliates (Protozoa, Ciliophora)

Abstract: Ciliates are a diverse species group of the Protozoa, and nuclear and mitochondrial genes have been utilized to discover new species and discriminate closely related species. The mitochondrial cytochrome c oxidase subunit 1 (CO1) gene has been used to discriminate metazoan species and has also been applied for some groups in the phylum Ciliophora. However, it is difficult to produce a universal primer as a standard barcode, because unlike metazoans, mitochondrial DNA sequences of ciliates are long and highly v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
4
27
0
Order By: Relevance
“…However we found that these multi-genes performed little better than a single gene marker in Parafavella yielding only two clusters. Nonetheless we agree with the comment of Santoferrara et al (2015) that because CO1 is much more variable than these nuclear genes it results in lower resolution at higher level of phylogeny (Park et al, 2018). In addition, genetic diversity of the CO1 can originate from heteroplasmy (i.e., intracellular polymorphism of mitochondrial genomes), nuclear encoded mitochondrial pseudogenes, and hybrids (Tautz et al, 2003;Zhao et al, 2013) The recent development of high-throughput sequencing technology has focused on attention on the variable regions (i.e., V4) in 18S to capture eukaryote diversity (Filker et al, 2015;Jung et al, 2015;Santoferrara et al, 2018;Stoeck et al, 2010).…”
Section: Nuclear Ribosomal Genessupporting
confidence: 89%
See 3 more Smart Citations
“…However we found that these multi-genes performed little better than a single gene marker in Parafavella yielding only two clusters. Nonetheless we agree with the comment of Santoferrara et al (2015) that because CO1 is much more variable than these nuclear genes it results in lower resolution at higher level of phylogeny (Park et al, 2018). In addition, genetic diversity of the CO1 can originate from heteroplasmy (i.e., intracellular polymorphism of mitochondrial genomes), nuclear encoded mitochondrial pseudogenes, and hybrids (Tautz et al, 2003;Zhao et al, 2013) The recent development of high-throughput sequencing technology has focused on attention on the variable regions (i.e., V4) in 18S to capture eukaryote diversity (Filker et al, 2015;Jung et al, 2015;Santoferrara et al, 2018;Stoeck et al, 2010).…”
Section: Nuclear Ribosomal Genessupporting
confidence: 89%
“…DNA sequencing was performed using three additional internal primers (18SF790v2: 5´-AAA TTA KAG TGT TYM ARG CAG-3´ and 18SR300: 5´-CAT GGT AGT CCA ATA CAC TAC-3´, 18SF1470: 5´-TCT GTG ATG CCC TTA GAT GTC-3´) and an ABI 3700 sequencer (Applied Biosystems, Foster City, CA, USA). For the conditions of CO1, it was as follows: denaturation at 94 for 1 min 30 s, followed by 40 cycles of denaturation at 98 for 10 s, annealing at 53 for 30 s, and extension at 72 for 1 min, and a final extension step at 72 for 7 min (for details and primers see Park et al, 2018). All PCR products were purified using a MEGAquick-spin Total Fragment DNA Purification Kit (iNtRON, Korea).…”
Section: Dna Extraction Pcr and Dna Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent decades, molecular phylogeny studies, especially those based on small subunit ribosomal RNA (SSU rRNA) gene sequence, have helped to answer important questions concerning evolution and phylogenetic relationships of some hypotrichous taxa 10,16,[23][24][25][26][27][28][29] . Recently, increasing studies have revealed phylogenetic analyses based on multigenes, e.g., SSU rRNA, internal transcribed spacers (ITS, including ITS1, 5.8S, ITS2) region, large subunit ribosomal RNA (LSU rRNA), and alpha tubulin gene could provide more robust interpretations than those using single gene information [30][31][32][33][34][35][36][37][38] . However, due to the under-sampling of both morphogenetic and molecular data, the phylogenetic relationships of a large number of taxa within this group are still confusing and unresolved.…”
mentioning
confidence: 99%